IMPLIKASI WORK-LIFE BALANCE DAN PENGEMBANGAN KARIR TERHADAP TURNOVER INTENTION KARYAWAN DI GRAND MIRAGE RESORT & THALASSO BALI - NI LUH PUTU SELLYNA APRILIANI DANISA PUTRI; I NYOMAN SUKA SANJAYA; GEDE SEDANA WIBAWA YASA (Universitas Mahasaraswati K. Mataram, 2024)
Human resources that are managed properly will determine whether a company is successful or not. With good human resources, employees will feel comfortable and safe, so as to reduce the level of turnover intention in the company. This research has a purpose to determine the effect between work-life balance and career development on employee turnover intention at Grand Mirage Resort & Thalasso Bali, using sampling technique, wich are called simple random sampling. So that the sample done as 78 employees. Data assessment techniques in this research carried out use descriptive statistical analysis, correlation analysis, multiple linear regression analysis, determination test and hypothesis testing. This research shows that “work-life balance at Grand Mirage Resort & Thalasso Bali has a negative and significant effect on employee turnover intention, as seen from the results of the t test with a significance value of 0.045. While career development has a negative and significant effect on employee turnover intention seen from the results of the t test with a significance value of 0.026. Work-life balance and career development have a simultaneous effect seen from the results of the f test with a significance value of 0.006”.